Morphogenesis of starfish polymersomes - Sun, Jiawei; Kleuskens, Sandra; Luan, Jiabin; Wang, Danni; Zhang, Shaohua; Li, Wei; Uysal, Gizem; Wilson, Daniela A. (Nature communications, 2023)
The enhanced membrane stability and chemical versatility of polymeric vesicles have made them promising tools in micro/nanoreactors, drug delivery, cell mimicking, etc. However, shape control over polymersomes remains a challenge and has restricted their full potential. Here we show that local curvature formation on the polymeric membrane can be controlled by applying poly( N -isopropylacrylamide) as a responsive hydrophobic unit, while adding salt ions to modulate the properties of poly( N -isopropylacrylamide) and its interaction with the polymeric membrane. Polymersomes with multiple arms are fabricated, and the number of arms could be tuned by salt concentration. Furthermore, the salt ions are shown to have a thermodynamic effect on the insertion of poly( N -isopropylacrylamide) into the polymeric membrane. This controlled shape transformation can provide evidence for studying the role of salt ions in curvature formation on polymeric membranes and biomembranes. Moreover, potential stimuli-responsive non-spherical polymersomes can be good candidates for various applications, especially in nanomedicine. Polymeric vesicles are promising candidates for use in a range of applications including drug delivery and cell mimics, however, control over the shape is still a challenge. Here, the authors report control over local curvature formation by addition of salt ions and stimuli responsive polymer to modulate its interaction with polymeric membrane.